Understanding the Factors Shaping Public Accountant’s Interest between the Accounting Students - Diajeng Fitri Wulan; Reni Oktavia; Usep Syaipudin (International Journal of Entrepreneurship, Business, and Creative Economy, 2024)
The accounting profession faces a challenge known as the CPA shortage, marked by a decline in employed accountants. This study, guided by Ajzen’s Theory of Planned Behavior (TPB), investigates factors influencing individuals’ intentions to become Certified Public Accountants (CPAs). As industry leaders seek to attract the next generation, our research explores the interplay between personal perceptions and external influences, emphasizing attitudes, subjective norms, and perceived behavioral control. This study involves undergraduate accounting students from 16 state universities in Sumatra, employing a Likert scale questionnaire and descriptive and correlation analyses. The results show positive attitudes toward the accounting profession, with variations in salary expectations. Subjective norms, including family, professors, and peers, significantly influence interest in becoming a public accountant. Perceived behavioral control factors, such as professional experience and job security, receive positive evaluation. Therefore, this study provides insights for institutions and policymakers, laying the groundwork for targeted initiatives to ensure a thriving future for the accounting profession despite technological advancements and evolving perceptions.